INFLUENCE OF PARENTAL INVOLVEMENT ON EARLY CHILDHOOD CARE AND EDUCATION (ECCE): THE TEACHERS’ PERSPECTIVES - AKSHAYA E (The Journal of Research ANGRAU, 2025)
This study conducted in the year 2022, investigates Anganwadi teachers’ perceptions of parental involvement in Early Childhood Care and Education (ECCE) in Kerala, India, focusing on the influence of teachers’ age and years of experience on parental involvement. Using a self designed rating scale, responses from 225 teachers were analysed through one-sample Z-tests and ANOVA to evaluate perceptions and demographic variations. The findings revealed a generally positive perception of parental involvement, with a mean perception score of 71.7% (z = 36.005, p < 0.001). Older teachers (mean = 22.25, SD = 2.70) and those with more experience (mean = 22.81, SD = 2.63 for 25-35 years) exhibited significantly more favourable attitudes toward parental involvement (p < 0.05). While most teachers (96.5%) agreed or strongly agreed that both parents and teachers should collaborate to enhance children’s readiness skills.Gaps in parental awareness were evident, with 73.3% of teachers perceiving a lack of awareness about ECCE. The study emphasises the need of professional development programs to strengthen teacher-parent collaboration, including training sessions, enhanced communication tactics, and active parental participation in decision-making